2020
DOI: 10.1111/inm.12789
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive reactivity among high‐risk individuals at the first and recurrent episode of depression symptomology: A structural equation modelling analysis

Abstract: Understanding the particular mechanisms by which vulnerability and capability factors influence cognitive reactivity (CR) can contribute to an enhanced capacity to adequately react to depression. However, few studies have explored the CR model. The main aim of the present study was to develop a model that specifies the predictive effects of CR for depression among individuals at high risk for first‐episode and recurrent depression. A national cross‐sectional, online study using convenience sampling was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…In our study, the LEIDS-RR-CV showed a Cronbach’s alpha, ICC, and marginal reliability with values > 0.7, indicating satisfactory internal consistency and temporal stability. Further, through CFA, we confirmed that a five-factor structure provided a good fit to the data and that all items were significantly loaded to the expected potential factors, similar to the results of the original version of the scale [ 21 ] and those of the Chinese version, which was validated among undergraduate students and women in remission from depression [ 23 , 29 ]. However, our results differ from those of the Spanish version of the LEIDS-RR, which presented a four-factor model [ 22 ], and the Persian version, which involved a sample of patients with depression from the general population and showed a six-factor model [ 15 ].…”
Section: Discussionsupporting
confidence: 70%
“…In our study, the LEIDS-RR-CV showed a Cronbach’s alpha, ICC, and marginal reliability with values > 0.7, indicating satisfactory internal consistency and temporal stability. Further, through CFA, we confirmed that a five-factor structure provided a good fit to the data and that all items were significantly loaded to the expected potential factors, similar to the results of the original version of the scale [ 21 ] and those of the Chinese version, which was validated among undergraduate students and women in remission from depression [ 23 , 29 ]. However, our results differ from those of the Spanish version of the LEIDS-RR, which presented a four-factor model [ 22 ], and the Persian version, which involved a sample of patients with depression from the general population and showed a six-factor model [ 15 ].…”
Section: Discussionsupporting
confidence: 70%
“…RTSCA’s five-factor structure was confirmed in one sample ( Liang and Cheng, 2012 ) and was replicated in Li et al (2017) . Wang et al (2010) conducted an EFA to explore CD-RISC-10’s one-factor structure, which was then verified by Cheng et al (2020) through CFA and in the case of RS-14, Tian and Hong (2013) reported two factors through EFA, which were verified in later structural equation modeling (SEM) analyses (e.g., Huang et al, 2020 ). Therefore, these measures were rated highest (i.e., “2”) for the factor structure criterion.…”
Section: Resultsmentioning
confidence: 88%
“…Developmental education mainly refers to the process of psychological counseling personnel on the basis of understanding the general laws of individual psychological development, giving certain education and counseling for the tasks faced by people at different stages so as to properly solve their psychological contradictions and give full play to their psychological potential, so as to promote the smooth development of their physical and mental health. This is a kind of routine, preventive, and improving education; the object of education is the normal development of the people [ 7 , 9 ].…”
Section: Mental Health Educationmentioning
confidence: 99%